Import Demand for Malaysian Palm-Based Oleochemical in the Netherlands - Nur Ain Mohd Hassan; Nur Syazwani Mazlan; Nur Nadia Kamil; Kamalrudin Mohamed Salleh; Onyegbule Queensley Chioma (International Journal of Supply Chain Management, 2018)
Malaysia is the second world largest palm oil producer. In 2016, Malaysia has produced 29.3% of world palm oil and 92.6% of the total production has been exported globally. Palm oil products are products that can be refined from the palm oil such as oleochemical and biodiesel. The main destination for Malaysian palm-based oleochemical products export is to the EU. As the Netherlands is the major palm-based oleochemical importer, this study attempts to examine the factors that influenced import demand of Malaysian palm-based oleochemical products in the Netherlands using the Autoregressive Distributed Lag (ARDL) Model. This study used annual data from 1984 to 2016. The results of the bound test indicated that there is a long-run relationship between the variables. The empirical results showed that domestic income, measured by the Gross Domestic Product (GDP) showed positive significant relationship as the GDP increases the demand for palm-based oleochemical from Malaysia also increases, while palm oil prices and total vegetable oils consumption have negative significant relationships with oleochemical demand. The evidence from this study indicated that demand from the Netherlands is significantly strong. Thus, the Malaysian government may need to further improve and reformulate the best strategy and policy to meet up with the increasing demand for palm-based oleochemical in the EU particularly in the Netherlands.